Challenges in the Implementation of Free Prior and Informed Consent for Indigenous Peoples in Indonesia's National Legal Regulation - Rahmi Jasim; Saldi Isra; Kurnia Warman; Hengki Andora (Green Publisher Indonesia, 2025)
This research discusses the challenges of implementing Free, Prior, and Informed Consent (FPIC) for indigenous peoples in national legal arrangements in Indonesia. FPIC is a principle that gives indigenous peoples the right to give consent to policies that affect their territories and resources freely, prior to full information, and without pressure. Although the FPIC rights of indigenous peoples are implicitly described and regulated in various national regulations, such as the 1945 Constitution, Forestry Law, Village Law, and environmental regulations slot zeus, these arrangements do not necessarily guarantee the protection of indigenous peoples' rights over their customary territories. Explicit legal arrangements are needed to guarantee indigenous peoples' FPIC rights over their customary territories. This is because in its implementation, the application of FPIC rights still faces various challenges such as conflicts of interest with the State's Right to Control (HMN), low understanding in the field, and gender injustice being the main obstacles. This study uses a normative juridical approach to identify differences between international and national legal arrangements, and offers recommendations to improve the protection and implementation of FPIC in Indonesia. The research emphasizes the importance of explicit legal arrangements to achieve justice, prosperity and harmony between indigenous peoples and the government.